UJI EFEKTIVITAS BAKTERI ANTAGONIS Pseudomonas flourescens DAN P. putida UNTUK MENGENDALIKAN P. solanacearum PENYEBAB PENYAKIT LAYU PADA TANAMAN MURBEI - Sitti Nuraeni; Abdul Fattah (PERENNIAL, 2007)
Pseudomonas solanacearum is a bacterial agent causing wilt disease on mulberry species and other woody plant in Indonesian. Biological control employing the antagonist bacteria such as P. fluorescens and P. Putida is a potential method. The aim of the research was to know the effectiveness of P. fluorescens and P. putida to suppress wilt diseases caused by P. solanacearum. The diseases control test with antagonist bacteria was conducted by immersion of root of seedlings in P. fluorescens and P. putida suspensions before planted in a growth medium inoculated by P. solanacearum with the all concentrations were 108 CFU/ml. The following parameters were observed: numbers of leaves, fresh and dry weights of leaves and severity of disease. The results of the effectiveness test showed that antagonist bacteria in the form of mixing of P. fluorescens and P. putida was the best, because they were capable to suppress wilt disease caused by P. solanacearum and increased productivity of mulberry leaves. keywords : antagonist bacteria, biological control, wilt disease